RELASI SOSIAL BURUH TANI DENGAN PEMILIK KEBUN SAWIT DI DESA BATHIN BETUAH KECAMATAN MANDAU KABUPATEN BENGKALIS - ', Winarti; ', Jonyanis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was conducted in Mandau District, Bengkalis Regency. This research aims to (1) determine the relationship between farm workers and oil palm plantation owners in Bathin Betuah village, Mandau sub-district, Bengkalis regency (2) Find out the impact of the relationship on the economic life of farm workers in Bathin Betuah village, Mandau sub-district, Bengkalis regency. This research used descriptive quantitative research methods, totaling 80 people with a sample of 67 respondents, sampling using the simple random sampling method. Based on the research results, it can be concluded that the form of relationship between farm workers and plantation owners is as follows: the range of social relations, density of social relations, norms of social relations, and trust show the highest level with the average showing a percentage in the high category. Factors that influence agricultural workers in improving welfare can be seen from several indicators: income and housing conditions. These two factors greatly influence the level of welfare of members, where as the income of agricultural workers increases, the level of housing conditions will be much better. Keywords: Social Relations, Farm Workers, Social Welfare